2005
DOI: 10.2134/jeq2005.0590
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate Losses in Subsurface Drainage from a Corn–Soybean Rotation as Affected by Fall and Spring Application of Nitrogen and Nitrapyrin

Abstract: Substantial amounts of NO3 from agricultural crop production systems on poorly drained soils can be transported to surface water via subsurface drainage. A field study was conducted from the fall of 1993 through 2000 on a tile-drained Canisteo clay loam soil (fine-loamy, mixed, superactive, calcareous, mesic Typic Endoaquoll) to determine the influence of fall vs. spring application of N and nitrapyrin [NP; 2-chloro-6-(trichloromethyl) pyridine] on NO3 losses from a corn (Zea mays L.)-soybean [Glycine max (L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
130
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 23 publications
16
130
3
Order By: Relevance
“…Previous studies have reported that high concentrations of nutrients generally associated with tile-fed drainage ditches from the Midwest could easily be transported to downstream surface waters [31][32][33]. Similar results have been reported for the impact of point source discharge on stream nutrient retention, where little sorption capacity is reported for sediment below point sources as compared to those upstream [20,34].…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have reported that high concentrations of nutrients generally associated with tile-fed drainage ditches from the Midwest could easily be transported to downstream surface waters [31][32][33]. Similar results have been reported for the impact of point source discharge on stream nutrient retention, where little sorption capacity is reported for sediment below point sources as compared to those upstream [20,34].…”
Section: Introductionsupporting
confidence: 79%
“…Inter-seasonal comparisons of PSI within individual ditches resulted in significant variations only in Box Ditch where Jan-Mar, Oct-Dec, and Jul-Sep PSI were significantly higher than Apr-Jun PSI (p < 0.008). Based on previous investigations that have associated high nutrient losses from tile drains [30][31][32], increased P concentrations in downstream sediments from tile outlets were expected. Nonetheless there were no specific patterns and statistical differences detected in the ability of benthic sediments to adsorb P from the ditch water when sediments collected upstream and downstream of tile drains were compared (p > 0.10; Figure 3).…”
Section: Phosphorus Uptake Of Upstream and Downstream Sedimentsmentioning
confidence: 99%
“…Studies have indicated that farmers often do not use the nutrient management tools available to them (Shepard, 2005;Osmond et al, 2012) or that regional practices may encourage application of N many weeks or months before crop uptake, which although useful managerially, may increase N losses (Randall and Vetsch, 2005;Bakhsh et al, 2006). Encouraging the most efficient timing, source, and placement of N fertilizer, three of the 4Rs of nutrient management (IPNI, 2017), is essential as we move forward in developing better rate recommendations.…”
Section: A Framework For Improving Nitrogenmentioning
confidence: 99%
“…Numerous studies have demonstrated production agriculture's impact on surface and groundwater nutrient concentrations (Rupert, 2008;Schilling and Libra, 2000). Although agriculture was not the only source of these nutrients, farming is an inherently leaky system and often constitutes a significant portion of the pollution (Preston and Brakebill, 1999;Randall and Vetsch, 2005;Alexander et al, 2008;White et al, 2014).…”
Section: Farmers' Use Of Nutrient Management: Lessons From Watershed mentioning
confidence: 99%